Exploring Adjectives in Health Advertorials - Sari Sujatna, Eva Tuckyta; Yuliawati, Susi (International Journal of English Literature and Social Sciences (IJELS), 2019)
This paper studies the types and functions of English adjectives in health advertorial of the Health magazine. From five health advertorials, the present research discovered adjectives that operated in two functions, namely attributive and predicative. The texts in the health advertorials had more attributive adjective than predicative adjective. The number of the attributive adjective was 98 while the predicative one was 31. The dominant type found in the attributive adjective was non-gradable adjective (52 out of 98 data) while in the predicative adjectives was gradable adjective (19 out of 31 data). Furthermore, from the total adjectives of 129 data, the present writers found 96 different adjectives that are classified into three categories, i.e. scalar, extreme, and limit. In both attributive and predicative adjectives, limit adjective was most frequent adjective. Besides, extreme adjective was discovered to be the least frequent category of adjective in the attributive adjective as well as the predicative adjective. It suggested that the use of attributive and predicative adjectives in terms of limit, scalar and extreme category tends to show the similar pattern. Additionally it is important to note that there are three adjectives that function both as attributive and predicative adjectives, i.e. BUSY, EASY, and IMPORTANT.